Instrumental activities of daily living function and cognitive status among Chinese older adults: a serial multiple mediation model - Huang, Sijie; Zhong, Wenjuan; Cheng, Qingzhou; Shuai, Yuxi; Zhu, Jiahui; Diao, Jiawei (Frontiers in Public Health, 2024)
Objective This study aimed to develop and validate a serial multiple mediation model to investigate the association between instrumental activities of daily living (IADL) function and cognitive status among older adults while exploring the underlying mechanisms. Methods This cross-sectional study involved 3,665 individuals aged 60 years and older who participated in the China Health and Retirement Longitudinal Survey (CHARLS). A serial multiple mediation model was utilized to explore the direct and indirect relationship between IADL function and cognitive status and whether sleep duration, social engagement, and depressive symptoms mediated this relationship. Results Decreased IADL function was associated with worse cognitive status [effect = −0.620, 95% CI: (−0.692, −0.540)]. Sleep duration, social participation (SP), and depressive symptoms all acted as mediators in the relationship between IADL function and cognitive status. Conclusion This study found both direct and indirect associations between IADL function and cognitive status, providing new insights into the effective prevention and intervention of cognitive decline among older adults.